2012
DOI: 10.3892/mmr.2012.1059
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Ang-1, IL-8 and TGF-β1 on the pathogenesis of COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a prevalent smoking-related disease for which no disease‑altering therapies currently exist. Airway remodeling is one of the most important mechanisms in the pathogenesis of COPD and is triggered by chronic inflammation mediated by angiopoietin-1 (Ang-1), interleukin-8 (IL-8) and transforming growth factor-β1 (TGF-β1). The aim of this study was to investigate the effects of Ang-1, IL-8 and TGF-β1 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Interestingly, TGF-β1 could delay the development of COPD, and help repair damage to the lungs of individuals who are at risk of developing COPD, preserving the decline of FEV 1 [20], [21]. Recent researches provided the levels of TGF-β1 were different at four stages of COPD with highest in stage IV, and inversely correlated with FEV 1 (% predicted) and FVC (% predicted) [22], [23]. Our study showed a slight decline in both active treatment groups after 180 days.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TGF-β1 could delay the development of COPD, and help repair damage to the lungs of individuals who are at risk of developing COPD, preserving the decline of FEV 1 [20], [21]. Recent researches provided the levels of TGF-β1 were different at four stages of COPD with highest in stage IV, and inversely correlated with FEV 1 (% predicted) and FVC (% predicted) [22], [23]. Our study showed a slight decline in both active treatment groups after 180 days.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Ang-2 might be a useful biomarker for COPD exacerbations and might help clinicians identify patients at risk of worse outcomes at the start of an exacerbation. Supporting this finding, another group found that blood levels of Ang-1 are reduced during COPD exacerbations and increased when patients are clinically stable [119]. As Ang-2 acts as an Ang-1 antagonist perhaps increased Ang-2 levels in these patients resulted in a reduction of Ang-1.…”
Section: Introductionmentioning
confidence: 76%
“…The main role of IL-8 in inflammation is the recruitment and activation of neutrophils, which produce more ROS and contribute to local tissue destruction at sites of inflammation (Hammond et al, 1995;Casini et al, 1997). Thus, it involves the pathogenesis of lung diseases associated with inflammation such as asthma (Ordoñez et al, 2000), chronic obstructive pulmonary disease (Gao and Zhan, 2012), fibrosis (Radomska-Le sniewska et al, 2010), and bronchiolitis (Kim et al, 2005). In this study, the abundance of IL-8 expression was highest among all the cytokines that are regulated by PHMG-phosphate (Fig.…”
Section: Discussionmentioning
confidence: 96%